O incentivo à inovação e o poder de compra estatal: Instrumentos da Lei Complementar n.º 182/2021 para contratações públicas de inovação - Kopczynski, Alexandre Henrique Moretti Cammarosano (2024)
Under the aegis of consecutive constitutional orders imposing on the Brazilian State the duty to encourage scientific, research, technology and, more recently, innovation, legal instruments for achieving this have been established going back to a brief legislative history that spans over half a century. Interestingly, despite a quantitatively and qualitatively relevant legal framework, historical records of increased investment in science and technology (S&T) and research, development and innovation (RD&I) activities, combined with Brazil's position among the largest economies in the world, the country is not considered an effective development environment in this matter. Supported by active state promotion action, one of the tools available and capable of high impact is the use of the State's purchasing power. Even though legislation has been in force for more than two decades that allows various applications of this purchasing power, with the qualification of constituting hypotheses of direct contracting, this incentive method continues to be considered undervalued by the national Public Authorities. More recently, two legislation dealing with bidding and administrative contracts brought new developments to the legal system, potentially capable of establishing a new phase in the use of the State's purchasing power so that, by acquiring innovative solutions, it promotes an environment for the development of innovation in national territory. Selected as a hypothesis to contribute to solving this problem, the legal framework for innovative entrepreneurship and startups, in force since the promulgation of Complementary Law No. 182/2021, and its new contractual hypotheses arising from the bidding process, will be the subject of investigation at in order to verify its compatibility with the current legal system and whether or not its normative provisions can, and in what way, assist in the greater adoption of public policies to promote innovation through state purchasing power